Fibroblast Growth Factor 23 and Blood Pressure in Older Adults: The Health, Aging, and Body Composition Study. Issue 1 (July 2020) - Drew, David A.; Katz, Ronit; Kritchevsky, Stephen; Ix, Joachim H.; Shlipak, Michael G.; Newman, Anne B.; Hoofnagle, Andrew N.; Fried, Linda F.; Sarnak, Mark; Gutiérrez, Orlando M.
Abstract : FGF-23 (fibroblast growth factor 23) regulates phosphorus and vitamin D. Elevated FGF-23 is associated with incident hypertension in young- and middle-aged adults, but there is limited data in older adults. Serum FGF-23 was measured using an intact ELISA assay in 2496 participants of the Healthy Aging and Body Composition Study. The association between FGF-23 and prevalent hypertension (self-reported and confirmed by use of antihypertensive medications) and number of antihypertensive medications was determined. The associations between FGF-23 and incident hypertension, and diastolic and systolic blood pressure trajectories were evaluated over 10 years. Models were adjusted for demographics, estimated glomerular filtration rate and albuminuria, cardiovascular disease risk factors, and measures of mineral metabolism. The mean (SD) age was 75 (3) years, with 51% women, and 40% black participants. The prevalence of hypertension at baseline was 75% and the mean systolic and diastolic blood pressures were 134 (21) mm Hg and 70 (12) mm Hg, respectively. The majority of participants without hypertension at baseline developed incident hypertension (576 of 1109 or 52%). In adjusted models, each 2-fold higher FGF-23 was associated with prevalent baseline hypertension (odds ratio=1.46 [1.24–1.73]) and greater number of blood pressure medications (IRR=1.14 [1.08–1.21]) but not with baseline diastolic or systolic blood pressure. In fully adjusted longitudinal analyses, a 2-fold higher FGF-23 was associated with incident hypertension (hazard ratio=1.18 [1.03–1.36]) and worsening systolic blood pressures (β=0.24 [0.08–0.40] mm Hg per year increase), but not with diastolic blood pressures (β=0.04 [−0.04 to 0.12] mm Hg per year increase). Higher FGF-23 concentrations are associated with prevalent and incident hypertension as well as rising systolic blood pressures in community-living older adults. Abstract : Supplemental Digital Content is available in the text.